Innovation, strategic renewal and its effect on small firm performance - Mickey Folkeringa; Joris Meijaard; André J. van Stel (Max Planck Institute of Economics, 2005)
In this paper, we investigate the relationship between strategic renewal and the performance of smaller firms (less than 100 employees). We use a panel of micro data on about 1000 Dutch firms. The dataset contains information on aspects of strategic renewal, including process innovation and knowledge management. In our regression analyses we explain the variation in firm performance and we explicitly control for reversed causality, business cycle effects, sector effects, and firm age. We find that market research, an active external network for knowledge acquisition and strategic efforts into the improvement of internal processes are positively related to turnover growth. Furthermore, codification of knowledge, cooperation with partner firms and the provision of training to employees directly relates to employment growth. The results emphasize the importance of both knowledge absorption and knowledge creation to the success of innovative efforts in small firms. We find that the impact of the various measures varies with firm size. One further notable finding is that the ownership of patents negatively impacts small firm performance, particularly for the smallest firms in our sample.
Keywords: L25; O33; 330; strategic renewal; growth of small firms; entrepreneurship; innovation